Unravelling the effect of environment on the genome of Sarda breed ewes using Runs of Homozygosity. (4th January 2022) - Cesarani, Alberto; Gaspa, Giustino; Correddu, Fabio; Dimauro, Corrado; Macciotta, Nicolò P. P.
Abstract: Natural adaptation and artificial selection have shaped the genome of modern livestock breeds. Among SNP‐based metrics that are used to detect signatures of selection at genome‐wide level, runs of homozygosity (ROH) are getting increasing popularity. In this paper, ROH distribution and features of a sample of 823 Sarda breed ewes farmed at different levels of altitude are analysed to investigate the effect of the environment on the patterns of homozygosity. A total of 46, 829 (33, 087 unique) ROH were detected. OAR2 exhibited the largest average number of ROH per animal. The most frequent ROH (OAR27, 38.9–44.2 Mb) was shared by 327. ROH length was statistically affected ( p < 0.001) by both the altitude and temperature of the place where the flock was located. The highest probability of a SNP falling in a ROH was observed for hill ewes, whereas the smallest one for mountain. A total of 457 SNP exceeded the 99th percentile of the ROH count per SNP distribution and were considered significant. These markers mapped in eight chromosomes and they clustered into 17 ROH islands, where 80 candidate genes were mapped. Results of this study highlighted differences in the ROH distribution and features among sheep farmed in flocks located at different levels of altitude, confirming the role of environmental adaptability in shaping the genome of this breed.